An atomistic investigation into the molecular effects of osteogenesis imperfecta like genetic mutations on biomaterial strength. (1st January 2012) - Dubey, Devendra; Tomar, Vikas
Osteogenesis imperfecta (OI) is a genetic disease marked by extreme bone fragility and is associated with mutations in tropocollagen (TC) molecule and changes in hydroxyapatite (HAP) mineral texture. Mutations in TC can manifest in both ways, substitution of polypeptide chains and point mutations of residues. This study presents a mechanistic view on the effects of OI mutations in TC on strength of model TC-HAP biomaterials with two different mineral distributions using three dimensional atomistic simulations. Analysis points out that substitution of residue sequences with higher number of side chain functional groups impart higher strength to the TC-HAP biomaterials. Results show that the effect of TC point mutations on the strength of TC-HAP biomaterials is insignificant. Instead, change in mineral distribution showed significant impact on the overall strength of TC-HAP biomaterials. Overall, study suggests that TC mutations manifest themselves by altering the mineral distribution during hydroxyapatite growth and nucleation period.